Reflections on the ocean economy development of Guangdong Province from the legal perspective: pathways, challenges and solutions - Wang, Peirui (Frontiers in Marine Science, 2025)
China possesses the largest and fastest-growing ocean economy globally. However, as its development reaches an advanced stage, the Chinese government recognizes that further progress requires pursuing not only quantity but also quality, thus proposing the concept of high-quality development of the ocean economy. Generating the highest marine gross domestic product (GDP) in China, Guangdong Province has pioneered legislative measures to foster this high-quality development. The Regulation of Guangdong Province on Promoting High-quality Development of the Ocean Economy aim to address specific challenges in the development of ocean economy in Guangdong Province, including an irrational industrial structure, inadequate governance mechanisms, an imbalance between economic development and environmental protection, and insufficient supply of key resources for ocean economic development. Nevertheless, Guangdong’s ocean economy development still confronts significant hurdles: deficient basic guiding concept for marine governance, an incomplete legal framework for marine governance, constrained comprehensive marine governance capabilities, insufficient support for key marine sectors, unbalanced regional progress, and a severe marine ecological situation. Consequently, Guangdong Province should clarify the basic guiding concept regarding marine governance, continue to improve the legal system of ocean economy, promote comprehensive marine governance, guide the development and upgrading of marine industries, strengthen regional legislative coordination, uphold the principle of green development, and proactively cope with climate change to promote high-quality ocean economic development.